Detección de virus respiratorios de la familia Coronaviridae en quirópteros urbanos de las provincias de Loja y Zamora Chinchipe - Parra Rivadeneira, Gabriela Steffania (2024)
Coronaviruses are a family of viruses that can cause highly pathogenic and zoonotic diseases in both animals and humans. One of the best-known members of this family is Coronavirus type 2 (SARS-CoV-2), the virus responsible for the COVID-19 pandemic that has had unprecedented global impact. Bats are recognized as natural reservoirs of coronaviruses, which means that these animals can harbor and transmit the virus asymptomatically. Given the ability of coronaviruses to mutate and evolve, it is essential to conduct ongoing surveillance of the presence and evolution of SARS-CoV-2 in bat populations, as this may provide valuable information for the prevention of future pandemics and the protection of public health. In Ecuador, there are few studies related to the approximation of the natural reservoirs of SARS- CoV-2. In view of this situation, an observational and cross-sectional study was established, focused on identifying the presence of SARS-CoV-2 and other coronaviruses in bats. Thus, a total of 126 bats were captured as a non-probabilistic sampling (by convenience) from the provinces of Loja and Zamora Chinchipe. In this research, we integrated molecular approaches such as the RT-qPCR technique (Quantitative Polymerase Chain Reaction). The results revealed an infection frequency of 13.49 % with SARS-CoV-2 across four different species (Desmodus rotundus, Anoura geoffroyi, Carollia perspicillata, Carollia sp). Additionally, we identified the presence of other coronaviruses (CoV) in 24.60 % of the samples, including viruses (HCoV-NL63, HCoV-HKU1, HCoV-229E, HCoV-OC43). Finally, we employed the full genome sequencing technique (ILLUMINA), revealing similarities ranging between 57 % and 78 % among the analyzed genomes and the reference sequence for SARS-CoV-2 in humans (NC_045512.2). The detection of genomic similarities between the analyzed genomes and the reference sequence for SARS-CoV-2 in humans underscores the importance of understanding viral diversity in bat populations, which may have implications for epidemiological surveillance and the understanding of potential zoonotic transmission of coronaviruses.